Photodegradation of toxic dye using Gum Arabic-crosslinked-poly(acrylamide)/Ni(OH)2/FeOOH nanocomposites hydrogel. (20th December 2019) - Naushad, Mu.; Sharma, Gaurav; Alothman, Zeid A.
Abstract: Healthy environment is necessary for growth and development of every living being. The deterioration of ecosystems due to discharge of inorganic and organic pollutants from different industries is one of the major problems. The major impact of these sources has been on our water resources. The literature studies revealed that from the age's humans are using various natural and synthetic materials for water purification. With Gradual development, these materials are modified and newer alternative materials are searched and fabricated. The present study relates to fabrication of novel Gum arabic-crosslinked-poly(acrylamide)/Ni(OH)2 /FeOOH nanocomposite hydrogel (GA-cl-poly(AAm)/Ni(OH)2 /FeOOH NCH) using simple copolymerization technique. The structural analysis of GA-cl-poly(AAm)/Ni(OH)2 /FeOOH NCH was performed by employing diverse modern analytical instrumentations such as transmission electron microscopy (TEM), X-ray diffraction (XRD), thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The HRTEM and SEM micrographs clearly demonstrated the engulfment of Ni(OH)2 and FeOOH particles within the nanohydrogel matrix. The photocatalytic performance of synthesized GA- cl -poly(AAm)/Ni(OH)2 /FeOOH NCH was investigated for photodegradation of methylene blue dye. All the parameters such as contact time, pH, concentration of methylene blue, NCH dosage and concentration of H2 O2 were optimized. It was noted that 75% methylene blue was degraded at optimized condition using GA- cl -poly(AAm)/Ni(OH)2 /FeOOH NCH in presence of H2 O2. Graphical abstract: Image 1056 Highlights: Gum Arabic-crosslinked-poly(acrylamide)/Ni(OH)2 /FeOOH nanocomposite hydrogel was synthesized using copolymerization technique. This nanocomposite hydrogel was used for the photodegradation of Methylene blue dye. 75% methylene blue dye was degraded at optimized condition. Efficient photocatalytic activity was observed even after 5 successive reuse.